Aqueous admixture for inorganic binder compositions
Patent Information
- Application Number
- JP2023559090
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-23
- Filing Date
- 2022-04-13
- Publication Date
- 2025-04-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing admixtures for inorganic binder compositions, particularly in additive manufacturing, require multiple additives that are difficult to combine, limit application flexibility, and pose challenges in mixing and curing, especially when formwork is not used.
An aqueous composition comprising anionic polymers, water-insoluble liquid defoamers, and optional set retarders, which reduces mixing water, increases open time, stabilizes viscosity, and enhances mechanical strength, facilitating additive manufacturing processes.
The composition improves the stability, reduces shrinkage, and enhances mechanical strength of inorganic binder compositions, enabling efficient and uniform application in additive manufacturing without formwork.
Smart Images

Figure 2022223410000001 
Figure 2022223410000002 
Figure 2022223410000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of aqueous admixtures for inorganic binder compositions such as concrete or mortar. In particular, the admixtures of the present invention are useful in the technical field of additive manufacturing. [Background technology]
[0002] Admixtures for inorganic binder compositions such as concrete or mortar are widely used to improve the quality of the fresh and hardened materials, e.g., to improve certain target properties such as strength, flowability, waterproofing, chemical resistance, etc. Admixtures typically contain more than one, e.g., two, three, or four, different chemicals, each of which serves to improve at least one of the target properties. Most of the admixtures currently available are used as aqueous solutions or dispersions.
[0003] In the technical field of mixing inorganic binder compositions, it is typically necessary to use various different additives to adjust the properties of the inorganic binder composition. This is the case, for example, when the inorganic binder composition is a cement-based composition, such as concrete or mortar. In the technical field of additive manufacturing, including 3D printing, of inorganic binder compositions, among others, various additives must be used. A typical requirement in the process of additive manufacturing is that the inorganic binder compositions must be pumped over long distances, distributed at high speed in layers, and harden quickly to support their own weight and the weight of subsequent layers applied on top. The latter is especially true when no formwork is used in the process of additive manufacturing. Various additives are needed to enable and facilitate these requirements. The dosing of various additives, such as dispersants, rheology modifiers, and strength enhancers, imposes additional requirements on the equipment. For example, it will be necessary to include several dosing units with pumps, valves, metering devices, mixing units, etc. Therefore, it is generally desirable to combine several additives into one admixture.
[0004] Admixtures containing cement dispersants and defoamers are disclosed, for example, in WO 2020 / 016072.
[0005] Suitable admixtures for use in additive manufacturing with cement-based materials are disclosed, for example, in WO 2020 / 187740.
[0006] Alternatively, it would be necessary to add all additives to the dry premix of the inorganic binder composition. However, this limits the types of additives that can be used, since they must be in a dry state and must be compatible with the other components of the inorganic binder composition during storage. Furthermore, when additives form part of the dry premix, their dosage cannot be easily adjusted according to the needs of a specific application. Summary of the Invention [Problem to be solved by the invention]
[0007] There is a continuing need for improved admixtures, especially improved admixtures suitable for additive manufacturing using inorganic binder compositions.
[0008] It is an object of the present invention to provide a useful admixture for inorganic binder compositions, especially for additive manufacturing applications. In particular, the admixture of the present invention provides the following advantages: (i) reducing the amount of mixing water required for the inorganic binder composition; (ii) increasing the open time of the inorganic binder composition; (iii) reducing shrinkage of the inorganic binder composition; (iv) facilitating mixing of the inorganic binder composition with the accelerator, in particular with liquid accelerators based on aluminum sulfate; (v) reducing and / or stabilizing the viscosity of the inorganic binder composition; (vi) reducing the air content of the inorganic binder composition; (vii) increasing the mechanical strength of the inorganic binder composition; (viii) facilitating the process of additive manufacturing using inorganic binder compositions; (ix) have increased stability One or more of the following should be provided: [Means for solving the problem]
[0009] Surprisingly, the above defined object is achieved at least partly, and in a preferred embodiment completely, by an aqueous composition as claimed in claim 1.
[0010] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments are the subject matter of the dependent claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In a first aspect, the present invention relates to an aqueous composition, preferably an aqueous emulsion, comprising, based on 100% by weight of the aqueous composition: (a) 12 to 55% by weight, preferably 15 to 50% by weight, in particular 20 to 45% by weight, of at least one anionic polymer selected from the group consisting of plasticizers, water reducers, superplasticizers, and workability retaining agents for inorganic binders, (b) 15 to 35% by weight, preferably 20 to 30% by weight, of at least one water-insoluble liquid defoamer, and (c) optionally 1 to 10% by weight, preferably 2 to 5% by weight, of at least one set retarder.
[0012] Water may be present in amounts up to a total of 100% by weight.
[0013] The aqueous composition of the present invention is preferably an aqueous emulsion. The aqueous emulsion can be an emulsion consisting of a dispersed phase dispersed in a medium such as an oil-in-water (o / w) emulsion or a water-in-oil (w / o) emulsion or a water-in-oil-in-water (w / o / w) emulsion. Preferably, the continuous phase of the aqueous emulsion of the present invention is water.
[0014] The aqueous composition, preferably the emulsion, of the present invention is preferably liquid. The aqueous composition, preferably the emulsion, is therefore preferably not in the form of a paste. The viscosity of the aqueous composition, preferably the emulsion, of the present invention is preferably less than 0.1 s. -1 When measured at a shear rate of 100 / s at 20°C, the viscosity is preferably 1 to 10,000 mPa·s.
[0015] The aqueous composition of the present invention comprises at least one anionic polymer selected from the group consisting of plasticizers, water reducers, superplasticizers, and workability retention agents for inorganic binders. Plasticizers, water reducers, superplasticizers, and workability retention agents for inorganic binders are known to those skilled in the art. Exemplary anionic polymers are lignosulfonates, sulfonated naphthalene formaldehyde condensates, sulfonated melamine formaldehyde condensates, sulfonated vinyl copolymers, polyalkylene glycols containing phosphonate groups, polyalkylene glycols containing phosphate groups, polycarboxylates containing polyalkylene glycol side chains, or anionic comb polymers.
[0016] According to an embodiment, the aqueous composition of the present invention comprises only one anionic polymer. According to a further embodiment, the aqueous composition of the present invention comprises two anionic polymers. According to yet a further embodiment, the aqueous composition of the present invention comprises three or more anionic polymers.
[0017] In both cases, the anionic polymer is + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group, preferably H +and / or an alkali metal ion, preferably -COO - , -SO2-O - , -O-PO(O - )2 and -PO(O - ) 2- groups.
[0018] According to a particularly preferred embodiment, the at least one anionic polymer is a copolymer having a polymeric backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomeric unit M1 and at least one side chain-bearing monomeric unit M2.
[0019] The ionizable monomer unit M1 in the copolymer preferably has the structure of formula I [ka] having The side chain carrying monomer unit M2 preferably has the structure of formula II [ka] having During the ceremony, R 1 are each independently -COOM, -SO2-OM, -O-PO(OM)2 and / or -PO(OM)2; R 2 , R 3 , R 5 and R 6 are each independently H or an alkyl group having 1 to 5 carbon atoms; R 4 and R 7 are each independently H, -COOM, or an alkyl group having 1 to 5 carbon atoms, Or, R 1 is R 4 forms a ring with -CO-O-CO-, M is, independently of each other, H +, an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; m=0, 1 or 2; p=0 or 1, Each X is independently -O- or -NH-; R 8 is the formula -[AO] n -R a where A=C2-C4-alkylene and R a H, C1~C 20 -alkyl group, -cycloalkyl group or -alkylaryl group, and n=2~250, especially 10~200.
[0020] Particularly preferred examples of copolymers of the present invention are polycarboxylate ethers or polycarboxylate esters (PCEs).
[0021] The molar ratio of monomer units M1 to monomer units M2 advantageously ranges from 0.5 to 6, in particular from 0.7 to 4, preferably from 0.9 to 3.8, and even more preferably from 1.0 to 3.7 or from 2 to 3.5.
[0022] More specifically, R 1 =COOM, R 2 =H or CH3, R 3 =R 4 = H. In this way it is possible to prepare copolymers based on acrylic or methacrylic acid monomers, which are of interest from an economic point of view. Furthermore, copolymers of this type in this context provide particularly good dispersing effects.
[0023] Also advantageously, R 1 =COOM, R 2 =H, R 3 =H and R 4 =COOM. The corresponding copolymers can be prepared based on maleic acid monomers.
[0024] The X group in the side chain carrying monomeric units M2 is advantageously -O- (=oxygen atom) in at least 75 mol %, in particular in at least 90 mol %, in particular in at least 95 mol % or at least 99 mol % of all monomeric units M2.
[0025] Advantageously, R 5 =H or CH3, R 6 =R 7 =H, and X=-O-. Thus, for example, it is possible to prepare copolymers from (meth)acrylic esters, vinyl ethers, (meth)allyl ethers or isoprenol ethers.
[0026] In a particularly advantageous embodiment, R 2 and R 5 are mixtures of 40-60 mol % H and 40-60 mol % -CH3, respectively.
[0027] In a further advantageous embodiment, R 1 =COOM, R 2 =H, R 5 =-CH3 and R 3 =R 4 =R 6 =R 7 =H.
[0028] In another advantageous embodiment, R 1 =COOM, R 2 =R 5 =H or -CH3, and R 3 =R 4 =R 6 =R 7 =H.
[0029] Particularly suitable copolymers are 1 = COOM;R 2 and R 5 are each independently H, -CH3, or a mixture thereof; R 3 and R 6 are each independently H or -CH3, preferably H; R 4 and R 7are each independently H or -COOM, preferably H.
[0030] R in side chain carrying monomer unit M2 8 The radical is R in the monomer unit. 8 It consists in particular to the extent of at least 50 mol %, in particular at least 75 mol %, preferably at least 95 mol % or at least 99 mol %, based on all of the radicals, of polyethylene oxide.
[0031] The proportion of ethylene oxide units, based on all of the alkylene oxide units in the copolymer, is in particular greater than 75 mol %, in particular greater than 90 mol %, preferably greater than 95 mol % and in particular 100 mol %.
[0032] More specifically, R 8 essentially has no hydrophobic groups, in particular no alkylene oxides having 3 or more carbon atoms. This means, in particular, that the proportion of alkylene oxides having 3 or more carbon atoms, based on all the alkylene oxides, is less than 5 mol%, in particular less than 2 mol%, preferably less than 1 mol% or less than 0.1 mol%. In particular, there is no alkylene oxide having 3 or more carbon atoms, i.e. the proportion is 0 mol%.
[0033] R a is preferably H and / or a methyl group. Particularly preferably, A=C2 alkylene and R a is H or a methyl group.
[0034] More particularly, the parameter n=10 to 150, especially n=15 to 100, preferably n=17 to 70, in particular n=19 to 45 or n=20 to 25. In particular, this achieves an excellent dispersion effect within the stated preferred ranges.
[0035] R 1 = COOM;R 2 and R 5 are, independently of each other, H, -CH3 or a mixture thereof; R 3and R 6 are each independently H or -CH3, preferably H; R 4 and R 7 are, independently of one another, H or -COOM, preferably H; whereby particularly preferred are copolymers in which X is -O- for at least 75 mol %, in particular for at least 90 mol %, in particular for at least 99 mol % of all monomer units M2.
[0036] It may further be advantageous if the copolymer comprises at least one further monomer unit MS which is chemically different from the monomer units M1 and M2. In particular, a large number of different further monomer units MS may be present. In this way, it is possible, for example, to further modify and adjust the properties of the copolymer with respect to a specific application.
[0037] Particularly preferably, the at least one further monomer unit MS has the formula III: [ka] (In the formula, R 5’ , R 6’ , R 7’ , m' and p' are R's as defined above in connection with the copolymer. 5 , R 6 , R 7 , m and p are the same as defined above; Each Y is independently a bond or -O-; Each Z is independently a chemical bond, -O-, or -NH-; R 9 are each independently an alkyl group, a cycloalkyl group, an alkylaryl group, an aryl group, a hydroxyalkyl group, or an acetoxyalkyl group, each having 1 to 20 carbon atoms. is a monomer unit.
[0038] The weight average molecular weight (M) of the copolymers of the present invention is measured by SEC against polyethylene glycol standards using 0.1N NaNO3 at pH 12 as the eluent. w ) is preferably 5,000 to 200,000 g / mol, more preferably 8,000 to 150,000 g / mol, particularly preferably 10,000 to 130,000 g / mol, and particularly preferably 12,000 to 80,000 g / mol.
[0039] The copolymers of the invention can be prepared by free radical copolymerization of the monomers M1 and M2 and optionally MS. Exemplary polymers are described, for example, in EP 2522680.
[0040] It is also possible to prepare the copolymers of the invention by polymer-analogous esterification and / or amidation of a polymer containing carboxylic acid groups with at least one polyalkylene glycol containing a hydroxyl or amino group at one end. Exemplary polymers are described, for example, in EP 1 138 697.
[0041] According to an embodiment, the aqueous composition of the invention comprises at least one anionic polymer having a non-random distribution of the monomeric units M1 and / or M2 in the direction along the polymer backbone. "Non-random distribution" is in this case understood to mean a non-statistical distribution of the monomeric units M1 and / or M2. This means that the ionizable monomeric units M1 and / or side chain-carrying monomeric units M2 are arranged in the copolymer, for example, in an alternating or block-type manner and / or in a gradient structure.
[0042] The structure of the copolymer can be analyzed and determined, for example, by nuclear spin resonance spectroscopy (NMR spectroscopy). 13 C and 1 By 1 H NMR spectroscopy it is possible in a manner known per se to determine the sequence of the monomer units in a copolymer on the basis of adjacent group effects in the copolymer and with statistical evaluation.
[0043] According to an embodiment, the copolymers of the invention are characterized by a non-random distribution of the monomers M1 and M2 in the copolymer in the form of blocks, with the ionizable monomer unit M1 being essentially present in at least one first block A and the side chain-bearing monomer unit M2 being essentially present in at least one second block B.
[0044] More specifically, any proportion of monomer units M2 present in the first block A is less than 25 mol %, in particular less than or equal to 10 mol %, based on all of the monomer units M1 in the first block A, and any proportion of monomer units M1 present in the second block B is less than 25 mol %, in particular less than or equal to 10 mol %, based on all of the monomer units M2 in the second block B.
[0045] At least one first block A advantageously comprises from 5 to 70, in particular from 7 to 40, preferably from 10 to 25, monomer units M1 and / or at least one second block B comprises from 5 to 70, in particular from 7 to 50, preferably from 20 to 40, monomer units M2.
[0046] According to a further embodiment, the copolymer of the invention is characterized by a non-random distribution of the monomers M1 and M2 in the copolymer in the form of a gradient structure in at least one section AA in the direction along the polymer backbone in terms of the molar ratio of ionizable monomeric units M1 to side chain-carrying monomeric units M2.
[0047] The term "gradient structure" or "concentration gradient" in the present case notably describes a continuous change in the local concentration of a monomer unit in at least one section in the direction along the copolymer backbone.
[0048] The concentration gradient can be, for example, essentially constant. This corresponds to a linear decrease or increase in the local concentration of each monomer unit in at least one section AA in the direction of the copolymer backbone. However, it is also possible for the concentration gradient to vary in the direction of the copolymer backbone. In this case, there is a non-linear decrease or increase in the local concentration of each monomer unit. The concentration gradient extends in particular over at least 10, in particular at least 14, preferably at least 20 or at least 40 monomer units of the copolymer. In contrast, abrupt or sharp changes in the concentration of the monomers, such as occurs, for example, in the case of block copolymers, are not referred to as concentration gradients.
[0049] The expression "local concentration" in the present context refers to the concentration of a particular monomer at a given point in the polymer backbone. In practice, the local concentration or the average of the local concentrations can be ascertained, for example, by measuring the monomer conversion during the preparation of the copolymer. In this case, the monomers converted within a particular period of time can be ascertained. The average local concentration corresponds, inter alia, to the ratio of the molar fraction of the particular monomer converted within the period in question to the total molar amount of the monomers converted within the period in question.
[0050] The monomer conversion can be determined in a manner known per se, for example with the aid of liquid chromatography, in particular high performance liquid chromatography (HPLC), and taking into account the amounts of monomers used. The structure of the copolymer can also be 13 C and 1 It can be determined by 1 H NMR spectroscopy as shown above.
[0051] Exemplary block or gradient copolymers are described, for example, in WO 2017 / 050902 and WO 2017 / 050907.
[0052] According to a preferred embodiment, the aqueous composition of the present invention comprises two anionic polymers, in particular two copolymers having a polymeric backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomeric unit M1 and at least one side chain-bearing monomeric unit M2. The two anionic polymers, in particular the two copolymers, differ in terms of their chemical composition and / or polymer structure.
[0053] According to a particularly preferred embodiment, the aqueous composition of the present invention comprises a first and a second anionic polymer, each anionic polymer being a copolymer having a polymer backbone and side chains attached thereto, each copolymer comprising at least one ionizable monomeric unit M1 and at least one side chain-bearing monomeric unit M2, wherein the first anionic polymer has a random distribution of monomeric units M1 and / or M2 in a direction along the polymer backbone, and wherein the second anionic polymer has a non-random distribution of monomeric units M1 and / or M2 in a direction along the polymer backbone.
[0054] The aqueous composition of the present invention comprises at least one water-insoluble liquid defoamer. The term "water-insoluble" in this document refers to the property of a substance that does not dissolve completely when more than 0.6 g is added to 100 g of distilled water at 20°C. It may be advantageous if the water-insoluble liquid defoamer is mixed with a non-ionic emulsifier before being added to the aqueous composition. A weight ratio of 80 to 99.5 parts of insoluble defoamer and 0.5 to 20 parts of non-ionic emulsifier giving 100 parts of premix is preferred. This may further improve the stability of the aqueous composition.
[0055] According to an embodiment, the water-insoluble defoamer is selected from the group consisting of white oils and / or hydrophobic silicas, which may comprise mineral oils, vegetable oils or waxes, silicones, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, which may be modified by alkoxylation or fluorination, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols.
[0056] The aqueous composition of the present invention optionally comprises at least one set retarder. A set retarder in the context of the present invention is an additive for an inorganic binder composition that slows down the hydration reaction of said inorganic binder composition after the addition of mixing water, compared to a control without the addition of any such set retarder. Set retarders are described in more detail in standard EN 934-2:2012-08, table 8.
[0057] According to an embodiment, the at least one set retarder is selected from the group consisting of sugar acids, sugars, sugar alcohols, and hydroxycarboxylic acids.
[0058] A "sugar acid" in the context of the present invention is a monosaccharide with a carboxyl group. It may belong to any of the classes of aldonic, urosonic, uronic or aldaric acids. Preferably, it is an aldonic acid. Examples of sugar acids useful in the context of the present invention include, but are not limited to, glyceric acid, xylonic acid, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, tartaric acid, mucic acid and saccharic acid. The sugar acid may be present in the form of a free acid or as a salt. According to an embodiment, the salt of the sugar acid may be a salt with a metal of groups Ia, IIa, Ib, IIb, IVb, VIIIb of the periodic table of the elements. Preferred salts of the sugar acid are salts of alkali and alkaline earth metals, iron, cobalt, copper or zinc. Salts with monovalent metals such as lithium, sodium and potassium are especially preferred.
[0059] In the context of the present invention, a "sugar" is a carbohydrate having an aldehyde group. In a particularly preferred embodiment, the sugar belongs to the monosaccharide or disaccharide classes. Examples of sugars include, but are not limited to, glyceraldehyde, threose, erythrose, xylose, lyxose, ribose, arabinose, allose, altrose, glucose, mannose, gulose, idose, galactose, talose, fructose, sorbose, lactose, maltose, sucrose, lactulose, trehalose, cellobiose, chitobiose, isomaltose, palatinose, mannobiose, raffinose, and xylobiose.
[0060] In the context of the present invention, a "sugar alcohol" is a polyhydric alcohol that can be derived from a sugar by redox reactions. Sugar alcohols therefore belong to the class of alditols. Examples of sugar alcohols include, but are not limited to, ethylene glycol, glycerol, diglycerol, threitol, erythritol, pentaerythritol, dipentaerythritol, xylitol, ribitol, arabitol, sorbitol, sorbitan, isosorbide, mannitol, dulcitol, fucitol, iditol, inositol, volemitol, lactitol, maltitol, isomalt, maltotriitol, maltotetraitol, and polyglycitol.
[0061] In the context of the present invention, a "hydroxycarboxylic acid" is a carboxylic acid that further comprises an OH moiety in the same molecule. Examples of hydroxycarboxylic acids include, but are not limited to, malic acid, citric acid, isocitric acid, tartronic acid, mandelic acid, salicylic acid, tartaric acid, and lactic acid. Hydroxycarboxylic acids can be present in the form of free acids or as salts. According to an embodiment, the salt of hydroxycarboxylic acid can be a salt with ammonium or with a metal of group Ia, IIa, Ib, IIb, IVb, VIIIb of the periodic table of the elements. Preferred salts of hydroxycarboxylic acids are alkali metal salts, alkaline earth metal salts, or ammonium salts.
[0062] Preferred set retarders are citric acid, tartaric acid, lactic acid, and gluconic acid and their salts. An especially preferred set retarder is sodium gluconate.
[0063] The aqueous composition of the present invention may further comprise additional components. The additional components may be selected from surfactants, cure accelerators, shrinkage reducing agents, colorants, rheology modifiers, pumping aids, biocides, and corrosion inhibitors. Advantageously, the aqueous composition further comprises a biocide in an amount sufficient to prevent bacterial and / or fungal growth.
[0064] According to some embodiments, the aqueous composition of the present invention further comprises 5-15% by weight, preferably 8-12% by weight, of a cationic linear polyamine, based on 100% by weight of the aqueous composition. Such cationic linear polyamines are available under the trade name Floquat. TM Available from the company SNF at:
[0065] According to an embodiment, the aqueous composition comprises, based on 100% by weight of the aqueous composition: (a) at least one anionic polymer which is a copolymer having 12 to 55, preferably 15 to 50, in particular 20 to 45% by weight of a polymer backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomer unit M1 and at least one side chain-bearing monomer unit M2; (b) 15 to 35% by weight, preferably 20 to 30% by weight, of a white oil, which may contain a mineral oil, a vegetable oil or a wax, and / or hydrophobic silica, at least one water-insoluble defoamer selected from the group consisting of silicones, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, which may be modified by alkoxylation or fluorination, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols, (c) optionally 1 to 10% by weight, preferably 2 to 5% by weight, of at least one set retarder selected from the group consisting of sugar acids, sugars, sugar alcohols, and hydroxycarboxylic acids; Includes.
[0066] In the above embodiments, water may be present in amounts totaling up to 100% by weight.
[0067] According to an embodiment, the aqueous composition comprises, based on 100% by weight of the aqueous composition: (a) at least one anionic polymer which is a copolymer having 12 to 55, preferably 15 to 50, in particular 20 to 45% by weight of a polymer backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomer unit M1 and at least one side chain-bearing monomer unit M2; (b) 15 to 35% by weight, preferably 20 to 30% by weight, of a white oil, which may contain a mineral oil, a vegetable oil or a wax, and / or a hydrophobic silica, one water-insoluble liquid defoamer selected from the group consisting of silicones, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, which may be modified by alkoxylation or fluorination, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols, (c) 1 to 10% by weight, preferably 2 to 5% by weight, of one type of setting retarder selected from the group consisting of sugar acids, sugars, sugar alcohols, and hydroxycarboxylic acids; (d) optionally, 5 to 15% by weight, preferably 8 to 12% by weight, of a cationic linear polymer; It consists of:
[0068] In the above embodiments, water may be present in amounts totaling up to 100% by weight.
[0069] According to an embodiment, the aqueous composition comprises, based on 100% by weight of the aqueous composition: (a) 12-55, preferably 15-50, especially 20-45 wt. % of two anionic polymers, the two anionic polymers being chemically and / or structurally different, wherein at least one, preferably both, of the two anionic polymers is a copolymer having a polymer backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomer unit M1 and at least one side chain-bearing monomer unit M2; (b) 15 to 35% by weight, preferably 20 to 30% by weight, of a white oil, which may be a mineral oil, a vegetable oil or a wax, and / or a hydrophobic silica, at least one water-insoluble liquid defoamer selected from the group consisting of silicones, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, which may be modified by alkoxylation or fluorination, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols, (c) optionally, 1 to 10% by weight, preferably 2 to 5% by weight, of at least one set retarder selected from the group consisting of sugar acids, sugars, sugar alcohols, and hydroxycarboxylic acids; It is an oil in water emulsion comprising:
[0070] In the above embodiments, water may be present in amounts totaling up to 100% by weight.
[0071] According to an embodiment, the aqueous composition comprises, based on 100% by weight of the aqueous composition: (a) 12 to 55, preferably 15 to 50, in particular 20 to 45 wt. % of a first and a second anionic polymer, each anionic polymer being a copolymer having a polymer backbone and side chains attached thereto, each copolymer comprising at least one ionizable monomer unit M1 and at least one side chain-bearing monomer unit M2, wherein the first anionic polymer has a random distribution of the monomer units M1 and / or the monomer units M2 in a direction along the polymer backbone, and a first and a second anionic polymer, the second anionic polymer having a non-random distribution of monomer units M1 and / or monomer units M2 in a direction along the polymer backbone; (b) 15 to 35% by weight, preferably 20 to 30% by weight, of a white oil, which may contain a mineral oil, a vegetable oil or a wax, and / or a hydrophobic silica, one water-insoluble liquid defoamer selected from the group consisting of silicones, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, which may be modified by alkoxylation or fluorination, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols, (c) 1 to 10% by weight, preferably 2 to 5% by weight, of one retarder which is sodium gluconate; (d) optionally, 5 to 15% by weight, preferably 8 to 12% by weight, of a cationic linear polyamine; It consists of:
[0072] In the above embodiments, water may be present in amounts totaling up to 100% by weight.
[0073] The aqueous composition of the present invention can be prepared by simply mixing all of the ingredients until a homogeneous composition, preferably a homogeneous emulsion, is obtained. However, the aqueous composition of the present invention can be prepared by the following steps: (a) mixing at least one set retarder, particularly sodium gluconate, with water; (b) combining at least one anionic polymer with the mixture obtained in step (a); (c) combining at least one water-insoluble defoaming agent with the mixture obtained in step (b). It is preferably prepared by:
[0074] Preferably, steps (b) and (c) are carried out using a high speed mixer or a gap homogenizer.
[0075] Optionally, the at least one anionic polymer can be admixed in step (b) in the form of a solution in water.
[0076] By following steps (a) to (c) as described above, particularly stable aqueous compositions, especially emulsions, are obtained.
[0077] It should be understood that all embodiments described above as preferred also relate to the preparation of aqueous compositions, preferably emulsions.
[0078] The aqueous compositions of the invention, preferably emulsions, are preferably prepared, handled and stored at temperatures between +5° C. and +60° C. Outside this temperature range there is a risk of the contained water freezing or evaporating.
[0079] The aqueous compositions, especially emulsions, of the present invention are particularly stable over long periods of time. Long periods in this context refer to weeks and months, for example up to 3 months, preferably up to 6 months, more preferably up to 12 months. Stable means that the aqueous compositions of the present invention do not show visible signs of phase separation. Visible signs can be, for example, the formation of droplets, creaming or settling of phases. It has been surprisingly found that at least one anionic polymer of the present invention stabilizes aqueous compositions, especially aqueous emulsions, of at least one water-insoluble liquid antifoam. Thus, at least one anionic polymer of the present invention can be used to stabilize aqueous compositions, especially aqueous emulsions, of at least one water-insoluble liquid antifoam. In the case of settling, Ostwald ripening, or phase separation, occurs, and the aqueous compositions, especially emulsions, of the present invention can be recycled and then used by simply stirring or shaking vigorously.
[0080] In a second aspect, the present invention relates to the use of an aqueous composition as described above in the preparation of an inorganic binder composition, in particular a binder composition comprising cement.
[0081] In the present context, an inorganic binder composition is a composition comprising at least one inorganic binder. Preferably, the inorganic binder composition further comprises at least one aggregate.
[0082] According to a particularly preferred embodiment, the inorganic binder is selected from the group consisting of cement, gypsum, lime, latent hydraulic binders, pozzolans and geopolymers. The cement is in particular a Portland cement as described in standard EN 197-1, a calcium aluminate cement as described in standard EN 14647 and / or a calcium sulfoaluminate cement. The term "gypsum" is meant to encompass the various forms of CaSO4, in particular anhydrous CaSO4, CaSO4 alpha and beta hemihydrate and CaSO4 dihydrate. The term "lime" is meant to encompass natural hydraulic lime, formulated lime, hydraulic lime and air lime as described in standard EN 459-1:2015. The pozzolans and potentially hydraulic materials are preferably selected from the group consisting of slags, clays, calcined clays, especially metakaolin, kiln dust, microsilica, fly ash, zeolites, rice husk ash, burnt oil shale, and natural pozzolans such as pumice and trass. The geopolymer is an alumo-silica polymer. One particular example of a geopolymer is furnace slag activated with water glass.
[0083] It may be particularly preferred that the inorganic binder composition comprises two or more inorganic binders. For example, the inorganic binder composition of the present invention may comprise a mixture of Portland cement and calcium aluminate cement and / or calcium sulfoaluminate cement. Another example is a mixture of Portland cement and gypsum, and calcium aluminate cement and / or calcium sulfoaluminate cement. Another example is a mixture of Portland cement, slag and calcium sulfoaluminate cement.
[0084] The inorganic binder composition of the present invention preferably further comprises an aggregate. The aggregate can be any material that does not react in the hardening reaction of the inorganic binder, especially in the hydration reaction. The aggregate can be any aggregate typically used for construction materials. Typical aggregates are, for example, rock, crushed stone, gravel, sand, especially quartz sand, river sand and / or crushed sand, slag, recycled concrete, glass, expanded glass, hollow glass beads, glass ceramics, volcanic rock, pumice, perlite, vermiculite, quarry waste, raw, calcined or fused earth or clay, porcelain, electrofused or sintered abrasives, calcination aids, silica xerogel. The aggregate can also be a fine aggregate or a filler such as crushed limestone, crushed dolomite, and / or crushed aluminum oxide. The aggregates useful in the present invention can have any shape and size typically encountered for such aggregates. A particularly preferred aggregate is sand. Sand is a naturally occurring granular material consisting of finely divided rock or mineral particles. It is available in a variety of forms and sizes. Examples of suitable sands are silica sand, limestone sand, river sand or crushed aggregates. Suitable sands are described, for example, in standards ASTM C778 or EN 196-1.
[0085] Optionally, the inorganic binder composition of the present invention further comprises additional additives common in the construction industry, such as surfactants, water reducers, redispersible polymer powders, fibers, set accelerators, set retarders, shrinkage reducing agents, colorants, rheology modifiers, pumping aids, biocides, and corrosion inhibitors. Preferably, the additional additives do not comprise any of the components of the aqueous composition of the present invention.
[0086] The inorganic binder composition may also include water.
[0087] The inorganic binder composition may therefore be a dry composition, such as a dry mortar or dry concrete, the term "dry" in this context referring to a water content of less than or equal to 5% by weight, more preferably less than or equal to 2% by weight, in particular less than or equal to 1% by weight.
[0088] The inorganic binder composition may also be in a wet state. Typically, the wet inorganic binder composition is in the form of a slurry in water. The wet inorganic binder composition preferably has a water:inorganic binder mass ratio of 0.1 to 0.8, preferably 0.25 to 0.6, in particular 0.3 to 0.5.
[0089] In a third aspect, the present invention provides an inorganic binder composition comprising: (a) at least one inorganic binder, preferably at least one cement; (b) at least one aggregate, preferably sand; (c) optionally at least one further additive; (d) optionally, water; (e) a mixture of the inorganic binder composition and the aqueous composition as described above in an amount of 0.5 to 10% by weight, preferably 1 to 5% by weight, based on the total dry weight of the inorganic binder composition; The present invention relates to a composition comprising:
[0090] It should be understood that all of the above embodiments also apply to the inorganic binder composition of the present invention.
[0091] It may be particularly preferred that the inorganic binder composition further comprises a hardening accelerator. Particularly suitable hardening accelerators are aqueous compositions based on aluminum sulfate. Such compositions are described, for example, in EP 1878713.
[0092] According to an embodiment, the inorganic binder composition comprises (each based on the total weight of the inorganic binder composition): (a) at least one inorganic binder selected from the group consisting of Portland cement, calcium aluminate cement, calcium sulfoaluminate cement, gypsum, lime or mixtures thereof in an amount of 10 to 66% by weight, preferably 15 to 50% by weight, in particular 20 to 45% by weight; (b) an aggregate, preferably sand, in an amount of 30-80% by weight, preferably 40-70% by weight; (c) a finely divided filler, preferably calcium carbonate, in an amount of 1 to 25% by weight, preferably 2 to 15% by weight; (d) optionally, a pozzolanic material and / or a latent hydraulic material in an amount of 1 to 25% by weight, preferably 2 to 10% by weight, (e) a mixture of the inorganic binder composition and the aqueous composition as described above in an amount of 0.5 to 10% by weight, preferably 1 to 5% by weight, based on the total dry weight of the inorganic binder composition; It comprises or consists of:
[0093] In a fourth aspect, the present invention relates to a method for preparing an inorganic binder composition as described above, comprising the steps of: (1) providing a dry mix comprising an inorganic binder, preferably at least one cement, at least one aggregate, preferably sand, and optionally at least one further additive; (2) optionally mixing the dry mix with water; (3) mixing the dry mix or a mixture of the dry mix and water with the aqueous composition described above; The present invention relates to a method comprising the steps of:
[0094] Suitable devices for mixing are not particularly limited and are known to those skilled in the art. Mixing is preferably performed semi-continuously or continuously. Particularly preferably, the mixing in step (3) is performed in a continuous mixing device, especially a dynamic mixer.
[0095] According to a particularly preferred embodiment, the method as described above is part of a process of additive manufacturing, preferably printing of 3D objects. Systems and methods for 3D printing of inorganic binder compositions are described, for example, in WO 2019 / 030328. The embodiments described herein are also suitable within the context of the present invention.
[0096] In the process of additive manufacturing, preferably 3D printing, the inorganic binder composition as described above is fed to a continuous mixer, preferably by means of a pump and a conveying line, in particular a hose. Preferably, the inorganic binder composition is a wet composition. This means that step (2) of the method as described above is preferably present. Such a wet composition can be conveyed more easily. Good conveyability is important for additive manufacturing, especially for 3D printing, since it is a prerequisite for uniform application. High pressure during conveying, especially in the hose, is disadvantageous, since it puts a great stress on the material, which will burst if loaded. A composition with good conveyability can prevent excessive build-up of pressure.
[0097] According to an embodiment, the aqueous composition of the present invention is added to the dry mix or to a mixture of dry mix and water just before or in the continuous mixing device. Preferably, the aqueous composition is added directly into the continuous mixing device.
[0098] The continuous mixer is preferably attached to a movable print head.
[0099] The print head preferably comprises a delivery nozzle for the layer-by-layer application of the inorganic binder composition. A continuous mixer is attached to the movable print head, preferably directly coupled to this delivery nozzle.
[0100] The dimensions and weight of the continuous mixer are preferably adapted to the size of the print head. It is therefore advantageous if the mixer in a printing installation for parts with relatively small geometries is also smaller than the mixer in a printing installation for parts with larger geometries, such as house parts or walls.
[0101] With a continuous mixer, the aqueous composition of the present invention is mixed very quickly, efficiently, and uniformly into the dry mix or into a mixture of dry mix and water, which is important so that the inorganic binder composition is uniform upon application layer by layer and cures quickly and evenly.
[0102] Mixing of the dry mix or the mixture of dry mix and water with the aqueous composition in the mixing zone is preferably carried out at a stirring shaft speed of preferably 500 to 3000 rpm, more preferably 650 to 2500 rpm, even more preferably 800 to 2000 rpm, most preferably 1000 to 1500 rpm.
[0103] Mixing at high speed produces rapid and efficient mixing of the dry mix or dry mix and water mixture with the aqueous composition.
[0104] The residence time of the inorganic binder composition in the mixer is preferably less than 10 s, more preferably less than 7 s, and very preferably less than 4 s. The residence time of the inorganic binder composition in the mixing device is the average time that the particles reside in the mixing device from the inlet to the outlet.
[0105] The inorganic binder composition of the present invention is preferably applied by means of a movable print head, which in particular has at least one delivery opening, which may be identical to the outlet of a continuous mixer, through which the hardenable material can be delivered.
[0106] The high sag resistance of the applied layer makes it unnecessary to bring the form panel to the delivery opening of the print head, however, in certain applications it may be advantageous to bring the form panel directly to the delivery opening.
[0107] At the delivery opening is preferably a delivery nozzle that shapes the delivered material. The shape should be adapted to the maximum particle size of the delivered material, but is not limited thereto.
[0108] The delivery nozzle preferably has a rectangular, square or circular shape. There may be further shaping elements attached to the delivery nozzle.
[0109] The print head can be moved in one, two or three spatial directions. A print head that can be moved in three spatial directions is particularly preferred. This allows shaped bodies of virtually any desired shape to be produced in a particularly simple manner.
[0110] Movement of the print head may be achieved by mounting the print head on a conventional robotic arm that can be moved in particular in one, two or three spatial directions.
[0111] The print head is preferably mounted on a 3-axis portal robot system, which allows for rapid printing of even larger features in flexible shapes.
[0112] Another possibility is to realize a movement in one, two or three spatial directions with a corresponding movement of a building volume, the building volume in this context being a volume, for example a surface, on which a structure is being built.
[0113] In a final aspect, the present invention also relates to a shaped body obtained by curing an inorganic binder composition as claimed above. In particular, the shaped article is produced in a process of additive manufacturing, in particular 3D printing.
[0114] Shaped bodies can be produced surprisingly quickly by layer-by-layer application. The height of the individual layers, typically measured in a direction substantially perpendicular to, and more particularly perpendicular to, the plane formed by the individual layers, is preferably from 1 mm to 200 mm, more preferably from 5 mm to 100 mm, more particularly from 10 mm to 50 mm.
[0115] The total height of the shaped body, or the thickness of all the individual layers of the shaped body taken together, is preferably from 0.01 m to 100 m or more, more preferably from 0.1 m to 80 m, more preferably even from 0.3 m to 30 m, more particularly from 0.5 m to 10 m.
[0116] While it is still functional, the surface of the shaped body can be smoothed, modified or specially modified with suitable tools. This can be done as part of a mechanical fabrication process or manually as a separate step. The surface can also be provided with a functional or decorative coating, for example with paint.
[0117] The feature can also be cut with a suitable tool while it is still functional: thus holes can be made in the feature, inter alia, window openings, doorways, conduit passages or cuts, inter alia, for subsequent work steps.
[0118] The structures can have almost any desired form: they are, for example, edifices, assemblies for edifices, architectural elements, masonry, bridges, columns, decorative elements such as rock formations, sand banks or statues, ponds, wells or gutters. In this case, they can represent solid or hollow shapes, with or without a base.
[0119] The shaped body can be produced directly on site and can no longer be moved after application. Alternatively, the shaped body can be produced at another site, in particular in a factory. This is preferably done on a base to which the shaped body does not adhere. After it has hardened, the shaped body can be transported to the desired site. EXAMPLES
[0120] Example 1 Aqueous compositions were prepared in the dosages shown in Table 1. The preparation of the compositions was as described for Aqueous Composition A1 below. The prepared compositions were stored in transparent plastic tightly closed containers at 20° C. The appearance of the compositions was checked after 7 days.
[0121] [Table 1]
[0122] It can be seen from Table 1 above that the aqueous composition according to the present invention has better stability.
[0123] Example 2 Inorganic binder composition C1 An inorganic binder composition (C1) was prepared by mixing 30 parts by weight of ordinary Portland cement (CEM I 52.5N), 50.5 parts by weight of sand (0.1-0.3 mm), 8 parts by weight of fine calcium carbonate filler (average particle size D50: 0.8 μm), 5 parts by weight of coarse calcium carbonate filler (average particle size D50: 400 μm), 6 parts by weight of calcined clay, and 0.5 parts by weight of calcium sulfate hemihydrate until visually homogeneous.
[0124] Aqueous composition A1 Aqueous composition A1 according to the present invention was prepared by dissolving 3 parts by weight of sodium gluconate in 16 parts by weight of water. 40 parts by weight of a 50% aqueous solution of an anionic polymer (polymethacrylate backbone with Mn=7,000 g / mol, methyl-terminated polyethylene glycol side chain with Mn=2,500 g / mol, carboxylate / side chain ratio=3) and 10 parts by weight of a 50% aqueous solution of a high charge density cationic linear polyamine were added to this solution and mixed using a high speed mixer. Then, 25 parts by weight of a water-insoluble defoamer (a mixture of silicone oil and mineral oil) were mixed using a high speed mixer.
[0125] Aqueous composition A2 Aqueous composition A2, according to the invention, was prepared identically to A1, except that sodium gluconate was not present.
[0126] Aqueous composition A3 Aqueous composition A3, not according to the invention, was prepared similarly to A1, except that no water-insoluble defoamer was incorporated.
[0127] Composition Testing Table 2 below shows the mixing scheme of C1 with compositions A1-A3, respectively. Mixing was performed by introducing each composition into a Hobart mixer in the amount shown in Table 2 below, adding mixing water in the amount shown in Table 2 below, and mixing at high speed at 20° C. until visually homogeneous. The mixing time required to visually homogeneous was recorded and reported in Table 2 below. The mixed material was used directly for testing.
[0128] Viscosities were measured with an Anton-Paar rotational rheometer at 20° C. at the shear rates shown in Table 2 below.
[0129] The open time was measured as the time when the strength exceeded 0.1 MPa using the method described in D Lootens et al., “Continuous strength measurements of cement pastes and concrete by the ultrasonic wave reflection method” in Construction and Building Materials, Vol 242, 2020.
[0130] The linear shrinkage was measured according to EN 12617-4 on a 40x40x160 mm prism within 16 hours after mixing.
[0131] The flexural and compressive strength was determined according to the standard DIN EN 1015-11.
[0132] [Table 2]
Claims
1. 1. An aqueous composition, preferably an aqueous emulsion, comprising, based on 100% by weight of said aqueous composition: (a) 12 to 55% by weight, preferably 15 to 50% by weight, in particular 20 to 45% by weight, of at least one anionic polymer selected from the group consisting of plasticizers, water reducers, superplasticizers, and workability retention agents for inorganic binders; (b) 15 to 35% by weight, preferably 20 to 30% by weight, of at least one water-insoluble liquid defoamer, and (c) optionally, 1 to 10% by weight, preferably 2 to 5% by weight, of at least one set retarder.
2. 2. The aqueous composition of claim 1, wherein the at least one anionic polymer is a copolymer having a polymeric backbone and side chains attached thereto, the copolymer comprising at least one ionizable monomeric unit M1 and at least one side chain-bearing monomeric unit M2.
3. 3. The aqueous composition according to claim 1 or 2, characterized in that the water-insoluble liquid defoamer is selected from the group consisting of white oils, which may comprise mineral oils, vegetable oils or waxes, and / or hydrophobic silicas, silicones which may be modified by alkoxylation or fluorination, alkyl esters of phosphoric or phosphonic acids, especially triisobutyl phosphate or tributyl phosphate, alkoxylated polyols, especially ethoxylated diols, fatty acid-based defoamers, especially mono- and diglycerides of fatty acids, and alkoxylated fatty alcohols.
4. 3. The aqueous composition according to claim 1, wherein the at least one set retarder is selected from the group consisting of sugar acids, sugars, sugar alcohols, and hydroxycarboxylic acids.
5. 3. The aqueous composition of claim 2, wherein the at least one anionic polymer has a non-random distribution of the monomeric units M1 and / or M2 in a direction along the polymer backbone.
6. The aqueous composition comprises first and second anionic polymers, each anionic polymer being a copolymer having a polymeric backbone and a side chain attached thereto, each copolymer comprising at least one ionizable monomeric unit M1 and at least one side chain-bearing monomeric unit M2, wherein: the first anionic polymer has a random distribution of the monomer units M1 and / or the monomer units M2 in a direction along the polymer backbone; and the second anionic polymer having a non-random distribution of the monomeric units M1 and / or the monomeric units M2 in a direction along the polymer backbone; The aqueous composition according to claim 1 , characterized in that
7. 7. The aqueous composition according to claim 5 or 6, characterized in that the non-random distribution of monomers M1 and M2 in the copolymer is in the form of blocks, the ionizable monomeric unit M1 being essentially present in at least one first block A and the side chain-bearing monomeric unit M2 being essentially present in at least one second block B.
8. 7. The aqueous composition according to claim 5 or 6, characterized in that the non-random distribution of monomers M1 and M2 in the copolymer is in the form of a gradient in at least one section AA in the direction along the polymer backbone with respect to the molar ratio of ionizable monomeric units M1 to side-chain-carrying monomeric units M2.
9. 7. The aqueous composition of any one of claims 2, 5 and 6, characterized in that the ionizable monomeric unit M1 in the copolymer has the structure of Formula I and the side chain carrying monomeric unit M2 has the structure of Formula II: 【Chemistry 1】 【Chemistry 2】 During the ceremony, R 1 Each independently represents -COOM, -SO 2 -OM, -O-PO (OM) 2 and / or -PO(OM) 2 and R 2 , R 3 , R 5 and R 6 are each independently H or an alkyl group having 1 to 5 carbon atoms; R 4 and R 7 are each independently H, —COOM, or an alkyl group having 1 to 5 carbon atoms; Or, R 1 is R 4 forms a ring with M is, independently of each other, H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; m=0, 1 or 2; p=0 or 1; Each X is independently -O- or -NH-; R 8 is represented by the formula -[AO] n -R a where A=C 2 ~C 4 -alkylene, R a is H, C 1 ~C 20 -alkyl group, -cycloalkyl group or -alkylaryl group, and n=2 to 250, particularly 10 to 200.
10. 7. The aqueous composition according to any one of claims 1, 2, 5 and 6, further comprising 5 to 15% by weight, preferably 8 to 12% by weight, of a cationic linear polyamine, based on 100% by weight of the aqueous composition.
11. 7. Use of the aqueous composition according to any one of claims 1, 2, 5 and 6 in the preparation of an inorganic binder composition, in particular a cement-containing binder composition.
12. An inorganic binder composition comprising: (a) an inorganic binder, preferably at least one cement; (b) at least one aggregate, preferably sand; (c) optionally at least one further additive; (d) optionally, water, and (e) The aqueous composition according to any one of claims 1, 2, 5 and 6 in an amount of 0.5 to 10% by weight, preferably 1 to 5% by weight, based on the total dry weight of the inorganic binder composition.
13. A method for preparing an inorganic binder composition comprising the steps of: The inorganic binder composition is (a) an inorganic binder, preferably at least one cement; (b) at least one aggregate, preferably sand; (c) optionally at least one further additive; (d) optionally, water, and (e) comprising an aqueous composition according to any one of claims 1, 2, 5 and 6 in an amount of 0.5 to 10% by weight, preferably 1 to 5% by weight, based on the total dry weight of the inorganic binder composition; The preparation method includes the following steps: (1) providing a dry mix comprising an inorganic binder, preferably at least one cement, at least one aggregate, preferably sand, and optionally at least one further additive; (2) optionally mixing the dry mix with water; (3) Mixing the dry mix or a mixture of the dry mix and water with an aqueous composition according to any one of claims 1, 2, 5 and 6.
14. 14. The method of claim 13, wherein the mixing in step (3) is performed in a continuous mixer.
15. 14. A method according to claim 13, characterized in that it is part of a process of additive manufacturing, preferably a process of printing 3D objects.
16. A shaped body obtained by curing the inorganic binder composition according to claim 12.